Estimation of Photosynthetic and Non-Photosynthetic Vegetation Coverage in Coal Mining Areas and Their Responses to Mining Activities Using Sentinel-2A Data - Pengfei Wang; Shidong Wang; Hebing Zhang; Yiheng Jiao; Menglin Liu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Nonphotosynthetic vegetation (NPV) is an important component of terrestrial ecosystems and also an important indicator of vegetation degradation, so it is important to accurately assess its cover. Based on the Sentinel-2A remote sensing data during 2016–2024, this article assessed the applicability of NDVI-fPV and DFI-fNPV in low hilly areas by establishing two sets of quantitative models; innovatively adopted GF-2 imagery and utilized supervised classification to remove pixel noise in Sentinel-2A to quantitatively estimate the photosynthetic and NPV cover in the coal mine area. On this basis, the spatial and temporal variations of photosynthetic and NPV cover and their correlation with mining disturbance in the coal mine area were further analyzed. The results showed that:First, the triangular spectral mixture model composed of NDVI and DFI was more capable of explaining the division of variability between PV, NPV and BS in the hilly terrain, and the correlation coefficient of fNPV estimated by DFI was R2 of 0.57, and the RMSE was 0.16, which was a high correlation. Second, the pixel selection after removing building and water body noise using supervised classification with GF-2 images is much purer and can significantly improve the recognition performance. Third, with the increase in the number of coal mining faces, the areas with high fNPV and medium-low fNPV show an expansion trend, while the rest of the areas contract, and the high fNPV areas are highly overlapping with the mining locations of the faces, which indicates that the mining activities negatively affect the vegetation cover of the region. In terms of the time series, the average fNPV of the mine site increases from 2016 to 2024, with an average annual growth rate of 0.57% percent. This article provides an important scientific basis for the monitoring and restoration of the ecological environment in the coal mine area, which not only helps to assess the long-term impacts of mining activities on vegetation ecosystems, but also provides reliable data support for the development of ecological restoration strategies in the mine area.